Strategi Kesiapan UMKM Bogor dalam Menghadapi Persaingan Global - Mokhamad Syaefudin Andrianto (Institut Pertanian Bogor, 2016)
Globalization give threat and opportunities for Bogor Small Medium Enterprises (SME’s). The purpose of this research is analyzing Bogor SME’s readiness to compete from aspects of knowledge, experience, business scale, innovation, direct and indirect networking. Entrepreneurs survey conducted in Bogor regency. Data processing used SmartPLS3. The result show experience, direct networking affect on innovation event experience has negative effect. Knowledge aspect, business scale and indirect networking do not have effect on innovation. In this case, Innovation has not been encourage SME’s readiness in global competition. Only knowledge has been significant encourage SME’s readiness to global competition